Study of mutation profile in myelofibrosis and response to low dose ruxolitinib: a tertiary care experience - Abinaya, D.; Rajendran, Aruna; Manoharan, Divya; Hari, Vandana G.; Yelugoti , Vikram (International Journal of Advances in Medicine, 2025)
Background: Myelofibrosis is a rare myeloid neoplasm characterized predominantly by anaemia and splenomegaly. Mutations in Janus kinase 2 (JAK2), calreticulin (CALR), and myeloproliferative leukaemia (MPL) play key roles. This study aimed to examine the demographic profile, transfusion dependency, and mutations (JAK2, CALR, and MPL) associated with myelofibrosis and to evaluate the response to Ruxolitinib treatment in these patients. Methods: This retrospective study included 30 patients at Madras Medical College, Chennai, from January 2022 to August 2024. Patients aged between 20 and 70 years at the time of diagnosis, primary myelofibrosis (PMF) or secondary myelofibrosis confirmed by clinical findings, laboratory tests, bone marrow biopsy, and genetic mutation such as JAK2 V617F, CALR, MPL, or triple-negative were included. Results: The mean age was 52.37±13.08 years, with splenomegaly and anaemia being common. Of the 30 patients, 73.3% were on Ruxolitinib and 59.1% were transfusion-dependent. CALR-positive and triple-negative patients were entirely transfusion-dependent, whereas JAK2-positive patients were predominantly non-transfusion-dependent (p<0.0001). Ruxolitinib treatment showed mild reduction on spleen size but significantly improved quality of life (p=0.031). Non-transfusion-dependent patients had better quality of life scores (p<0.0001). Conclusions: Genetic testing, including both driver and non-driver mutations, plays a crucial role in the diagnosis, prognosis, and treatment of myelofibrosis. Transfusion dependency and anaemia severity are negative prognostic factors, while Ruxolitinib improves the quality of life.